Balancing Time: Seeing the past, present, future and other time in the productions of Siamsa Tíre, the National Folk Theatre of Ireland - Kearney, Daithí (Schweizer Jahrbuch für Musikwissenschaft, 2026)
For over five decades, Siamsa Tíre, the National Folk Theatre of Ireland sought to balance a sense of past, present and future in their work as part of an effort to preserve local traditions and remain relevant to contemporary theatre audiences. Although early productions from the 1960s such as Fadó Fadó (1968) focused on the representation of rural Irish life, akin to much of the early twentieth century Irish drama influenced by cultural nationalism, developments from the 1980s in particular sought a greater balance between remembering past practices of intangible cultural heritage and seeking to devise and develop new work that incorporates influences from changes in society and arts practice. Many of the productions utilized a sense of time as a narrative device, inviting audiences back in time or into another realm, as a method to engage a contemporary audience. Reflecting on developments on- and off-stage, in this paper I identify three aspects of time in the work of Siamsa Tíre: the narrative device that invites the audience ‘back in time’, the representation of the passage of time in mythological stories, and the responsiveness of the company to the time in which it exists.